Marital status and survival in cancer patients: A systematic review and meta‐analysis - Kaja Krajc; Špela Miroševič; Jakob Sajovic; Zalika Klemenc Ketiš; David Spiegel; Gorazd Drevenšek; Martina Drevenšek (Cancer Medicine, 2023)
Abstract Background In recent years, authors have repeatedly reported on the significance of social support in cancer survival. Although overall the studies appear to be convincing, little is known about which types of social support promote better survival rates, and which subgroups of cancer patients are more susceptible to the benefits of it. The aim of this study was to identify, organize, and examine studies reporting on the significance of social support in cancer survival. Methods The PubMed, CINAHL and EBSCO databases were searched using the keywords social support/marital status, cancer, and survival/mortality. Where possible we used a meta‐analytical approach, specifically a random effect model, in order to combine the results of the hazard ratios in studies from which this information could be obtained. When interpreting clinical relevance, we used the number needed to treat (NNT). Results Better survival was observed in married patients when compared to unmarried (single, never‐married, divorced/separated, and widowed) in overall and cancer‐specific survival. Gender group differences showed that the association was statistically significant only in cancer‐specific survival when comparing divorced/separated male and female cancer patients (p < 0.001), thus confirming results from the previous meta‐analysis. Conclusions Being unmarried is associated with significantly worse overall and cancer‐specific survival. The most vulnerable group found in our study were divorced/separated men. The results of this review can motivate physicians, oncologists, and other healthcare professionals to be aware of the importance of patients' social support, especially in the identified sub‐group.